The Effect of Segmentation, Targeting, Positioning on Purchasing Decisions of Baperchips Brownies Chips MSMEs Products - Windi Sari; Ahmad Albar Tanjung (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
The purpose of this study was to find out whether there is an effect of Segmentation, Targeting, and Positioning on purchasing decisions at Baperchips MSMEs Products. The sample in this study was 100 people. The method used in this study was a quantitative method. This study used primary data, primary data in this study were obtained from respondents’ answers through interviews, observation, and questionnaires. The power analysis used in this study is the Structural Equation Model with Smart PLS. The results of this study indicate that partial Segmentation has a positive but not significant effect on purchasing decisions, Targeting has a positive and significant effect on purchasing decisions, and Positioning has a positive and significant effect on purchasing decisions.